A study of the pathogenesis of fetal damage caused by ethanol in the experimental mouse - Thompson, Patricia Anne Curgenven (Division of Chemical Pathology, 2018)
In an attempt to determine mechanisms of certain aspects of ethanol- induced fetal damage, I have established a mouse model of the fetal alcohol syndrome based on the work of Chernoff (1977), using inbred C3H mice. Ethanol or its metabolite, acetaldehyde, was administered to female mice prior to and throughout gestation. Ethanol in doses of 6%, 10% and 20% ethanol derived calories and acetaldehyde 3. 9 mg and 11. 8 mg were administered daily in a nutritionally balanced liquid diet. An acute dose study was also undertaken, in which pregnant C3H mice were given. "binge" doses of 1ml of a 7. 35% solution of ethanol, twice daily through an orogastric tube, on days one and eight or four and twelve of gestation. The mice were sacrificed on day eighteen of gestation and the fetuses weighed and examined macroscopically. Some were sectioned using Wilson's method of free-hand razor blade sectioning (Barrow and Taylor, 1969), and the skeletons of the others were examined using a modified Dawson's method of skeletal preparation (Richmond and Bennett, 1938). A separate in vitro model based on the work of New (1967) was established, in which embryos of eight or nine days' gestation were explanted with visceral yolk sac intact from normal C3H mice. They were cultured for twenty-eight hours in rat serum containing various concentrations of ethanol or acetaldehyde (ethanol 1500, 3000 and 6000mg/l and acetaldehyde 7.4, 19. 7 and 39.4mg/l). During the last four hours of the culture period the embryos were labelled with one microcurie of tritiated thymidine (specific activity 5curies/mmol). At the end of the culture period the embryos were assessed morphologically, and then prepared for liquid-scintillation counting to determine DNA synthesis by measuring tritiated thymidine uptake. Small numbers of embryos from each group were used for autoradiographic studies in an attempt to quantitate the uptake of label in the various parts of the embryo. I found that ethanol given in chronic dosage in vivo was embryotoxic in all three doses studied. There was no evidence of ma tern al toxicity other than hyperactivity at the highest dose used and maternal jaundice in a small number of the 10% EDC and 20% EDC mice. Acetaldehyde given in chronic dosage in vivo produced no toxic effects on mothers or fetuses, other than a reduction in placental weights. Acute "binge" ethanol dosage of mothers on days one and eight or four and twelve of gestation did not appear to have any adverse effects on mothers or fetuses, apart from changes in placental weights. These findings should be viewed with caution, as the in vitro studies did not produce a corresponding result. In the latter study there was a marked time-related response, particularly for acetaldehyde. Ethanol given in vitro produced little evidence of toxicity except at dose levels which in the corresponding in vivo situation were extremely toxic to the mothers. Acetaldehyde, given in vitro in minute fractions of the harmless doses given to mothers in vivo, proved to be highly toxic to 8-day embryos and relatively non-toxic to 9-day embryos. This difference in sensitivity indicates that there must be some protective factor intervening between eight and ten days gestation - possibly the developing placenta may have a role here. From these findings I would suggest that acetaldehyde is a true teratogen, and the abnormalities produced in the chronic ethanol in vivo study were probably largely due to the action of acetaldehyde.